2014
DOI: 10.2337/db13-1965
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage HIF-2α Ameliorates Adipose Tissue Inflammation and Insulin Resistance in Obesity

Abstract: In obesity, adipose tissue macrophages (ATMs) play a key role in mediating proinflammatory responses in the adipose tissue, which are associated with obesity-related metabolic complications. Recently, adipose tissue hypoxia has been implicated in the regulation of ATMs in obesity. However, the role of hypoxia-inducible factor (HIF)-2α, one of the major transcription factors induced by hypoxia, has not been fully elucidated in ATMs. In this study, we demonstrate that elevation of macrophage HIF-2α would attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 45 publications
(79 reference statements)
4
87
0
Order By: Relevance
“…Examining the role of HIF in ATMs has shown that in vitro exposure to hypoxia increased the expression of IL-6 and IL-1␤ but not TNF-␣, which strongly supports our findings (18). Additionally, Choe et al (47) have shown that knocking down HIF-2␣ enhanced palmitate-induced IL-6 expression, which is also in agreement with our findings. Collectively, although HIFs modulate various pro-inflammatory pathways, including IL1␤ expression, our data indicate that, during acute exposure to 1% O 2 , HIFs are not primarily responsible for potentiating the production of palmitate-induced, pro-inflammatory cytokines in macrophages.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Examining the role of HIF in ATMs has shown that in vitro exposure to hypoxia increased the expression of IL-6 and IL-1␤ but not TNF-␣, which strongly supports our findings (18). Additionally, Choe et al (47) have shown that knocking down HIF-2␣ enhanced palmitate-induced IL-6 expression, which is also in agreement with our findings. Collectively, although HIFs modulate various pro-inflammatory pathways, including IL1␤ expression, our data indicate that, during acute exposure to 1% O 2 , HIFs are not primarily responsible for potentiating the production of palmitate-induced, pro-inflammatory cytokines in macrophages.…”
Section: Discussionsupporting
confidence: 83%
“…HIFs have been implicated in adipose tissue inflammation and insulin resistance (9,47). For this reason, we speculated that the potentiation of palmitate-induced, pro-inflammatory cytokines in hypoxic macrophages may be mediated by HIF-1␣ and HIF-2␣.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HIF-2a haplodeficiency in mice on a normal chow diet also did not report any differences in glucose tolerance or insulin sensitivity. 25 These findings are consistent with our study in the HIF-2a OE mice on chow diet. However, upon HFD feeding, HIF-2a heterozygous-null mice exhibited more aggravated glucose intolerance and insulin resistance compared to WT mice.…”
Section: Pancreas Specific Overexpression Of Hif-2a Does Not Alter Glsupporting
confidence: 83%
“…24 In macrophages, overexpression of HIF-2a improved insulin resistance in adipocytes. 25 To our knowledge the specific in vivo role of HIF-2a overexpression in b cells has not been identified to date. In the present study, we used a tissue specific approach to overexpress HIF-2a in pancreatic b cells to determine its role in glucose homeostasis under basal conditions and during metabolic challenge by high fat diet (HFD) feeding.…”
Section: Introductionmentioning
confidence: 99%
“…M2 polarization also can be advantageous in adipose tissue macrophages because hypoxia-inducible factor-2a, expressed mainly in M2-like adipose tissue macrophages, ameliorates adipose tissue inflammation and insulin resistance in obesity (2).…”
mentioning
confidence: 99%